Study of glycoluril and its derivatives by ¹H and ¹³C NMR spectroscopy - Panshina, S.Yu.; Ponomarenko, O.V.; Bakibaev, A.A.; Malkov, V.S.; Kotelnikov, O.A.; Tashenov, A.K. (KSU Publ., 2020)
Bicyclic bisureas, especially 2,4,6,8-tetraazabicyclo[3.3.0.]octan-3,7-dione (glycoluril), have a special place in chemistry of heterocyclic compounds. The carbamide fragment in glycoluril structure determines the properties of the molecule, which are due to the presence of two reaction centers (NH-groups and C=O-groups) in C=O-groups) the molecule. In this work, we analyzed the proton and carbon chemical shifts of glycoluril and its derivatives (86 compounds) in the NMR spectra to reveal the effect of the donor-acceptor substituents on the changes in the electron density in the bicyclic framework from the position of symmetry and asymmetry. A general analysis of the 1H and 13C NMR spectra of glycolurils makes it possible to accurately determine the spatial configurations of molecular symmerty, in the presence of which (σ1 and / or σ2) the enantiotopic hydrogen and carbon atoms of the bicyclic framework are manifested by equivalent signals. Also, according to the 1H and 13C chemical shifts in the NMR spectra, glycolurils with electron-acceptor substituents can be clearly distinguished by the shielding of carbon atoms of C=O-groups, and with electron-donating substituents by the deshielding of CH-CH-carbons, due to the rearrangement of electron density and the occurrence of local paramagnetic contributions owing to anisotropy.
Гликолурил жəне оның өнімдерін 1H жəне 13C ЯМР спектроскопия əдісімен зерттеу
Исследование гликолурила и его производных методами 1H и 13C ЯМР спектроскопии
Keywords: glycoluril; NMR; chemical shifts; symmetry; enantiotopic atoms; shielding; deshielding; X-ray diffraction